An Evaluation of Microbial Flora, Alkaline Phosphatase and IL-8 Levels in GCF of Orthodontic Patients with Self-Ligating and Conventional Brackets - Nassar EA; Almasoud NN; Al-Qurashi MS; Alsulaiman AA; Hassan KS (Dove Medical Press, 2021)
Essam Abdelalim Nassar,1 Naif Nasser Almasoud,1 Maher Sulaiman Al-Qurashi,2 Ahmed A Alsulaiman,1 Khalid Sadiaq Hassan3 1Department of Preventive Dental Sciences, College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2Department of Microbiology, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, KSA, Saudi Arabia; 3Department of oral Medicine and Periodontology, College of Dentistry, Al-Azhar University, Assiut, EgyptCorrespondence: Essam Abdelalim NassarDepartment of Preventive Dental Sciences, College of Dentistry, Imam Abdulrahman Bin Faisal University, Saudi ArabiaTel +966542941098Email e_abdelalim@yahoo.comPurpose: To compare the microbial flora, alkaline phosphatase (ALP) and interleukin-8 (IL-8) levels during orthodontic treatment with self-ligating brackets versus conventional brackets.Patients and methods: Forty patients were included in this study and distributed equally between two groups. One group received conventional edgewise brackets while the other group received DAMON self-ligating brackets. Periodontal parameters were recorded and biochemical and microbial analyses were conducted before bonding (baseline), and 14, 30, and 45 days after bonding. Paired t-test was performed to estimate the intergroup differences from the baseline at the various time points; unpaired t-test was used for intragroup comparisons.Results: A significantly higher prevalence of gram-negative as well as gram-positive microorganisms was found in the group with conventional brackets than that with self-ligating brackets. Alkaline phosphatase (ALP) activity and interleukin-8 (IL-8) levels were significantly higher in the gingival crevicular fluid of the group with conventional brackets than that with self-ligating brackets.Conclusion: The conventional bracket-ligature technique exhibited an increase in IL-8 levels, ALP activity, and microbial colonization compared with that of the self-ligature technique. Accordingly, self-ligating brackets are recommended in orthodontic patients to improve periodontal health and minimize damage outcomes of periodontal tissue interventions.Keywords: dentistry, orthodontics, alkaline phosphatase, jnterlukin-8, orthodontic tooth movement, periodontal parameters